MOTHER'S EXPERIENCE IN GIVING EXCLUSIVE BREASTFEEDING: A SCOPING REVIEW - Dian Shofia Reny Setyanti; Dewi Rokhanawati (International Journal Labs, 2022)
Exclusive Breastfeeding is to offer only breast milk without additional food until the baby is 6 months old, except for medicine and vitamins. Breast milk is still given until the age of 2 years. Target of the Ministry of Health's Strategic Plan in offering Exclusive Breastfeeding which has not yet reached the target in 2015-2019. Various impacts that will arise because breast milk is not given, for example diarrhea and ARI. The purpose of this article is to conduct an evidence-based review related to the experience of mothers in exclusive breastfeeding. This scoping review method uses the Arksey & O'Malley framework which consists of 5 stages, namely identification of review questions, identification of relevant studies, study selection, data mapping (data charting), and compiling, summarizing, and reporting results. Search articles through Ebsco, Pubmed, and Wiley Online Library databases. Selection of articles with Prism Flow Chart which is used to describe the flow of article search, perform Critical Appraisal to assess the quality of articles. The results based on the 8 articles obtained, obtained 7 articles with Grade A and 1 article with grade B. Furthermore, 2 themes were obtained, namely factors that affect the success of exclusive breastfeeding and obstacles that affect exclusive breastfeeding. The conclusion of the 8 articles, only 1 article was found that discussed the condition of the mother and the support of health workers in the factors that influence the success of exclusive breastfeeding. And only 1 article was found that discussed the condition of mothers in the barriers to exclusive breastfeeding.